Visual Variety on the Change of Bridal Ornamental Kebaya Clothes for Generation Z in Sumenep, Madura - Soelistyowati, Soelistyowati (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research discussed one of the problems with Indonesian cultural heritage in this digital world like nowadays. It was the form of decoration on wedding dresses in the Sumenep-Madura area, which was rarely seen in Indonesia, especially wedding dresses. They made some modifications to the traditional Madura wedding dress to look more modern. In this digital world where people could easily access everything, generation Z preferred cultural products from abroad rather than local culture. The research applied a qualitative method with descriptive analysis of document analysis and library sources with Java-Madura boundaries. The interviewes were conducted with cultural experts, young women, especially those who were about to get married, and creative industry players of bridal kebaya. The aim of the research was to determine the interest of young people in the decoration of wedding dresses. The research used the theory of triadic interplay concept analysis of forms, visuals and characters, and ornamentation as a visual object of tradition that was expected to be able to transform not only as an object of decoration but also as an object of education that gave value and meaning to its users. The research finds it important to study the changes in decoration to be maintained by revitalizing it without leaving the old form based on design work that can be applied through creation. By using quantitative methods through experiments with detachable techniques, fashion design concepts with meaning values can be conveyed in each form, motif, and ornament. So that the younger generation accepts and likes changes in decoration with modern forms that can practically be mixed and matched.